STUDI PEMANFAATAN KULIT KERANG SEBAGAI BAHAN PENYUSUN PADA PEMBUATAN LEM KACA - M. Nadjib M. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Shellfish are ones of sea’s product which use as food, and shell part as a waste. This experiment was done to utilize shell as main product in glass adhesive together whit Arabic gum and white part of chicken egg as sticky substances. The shell contended about 76,64% of CaCO3 which could repair adhesive working to increase shear strength and curing time. Adhesive were made by variation composition in gram number of shell powder and Arabic gum. The best composition was obtain on 68.45% of shell; 8.22% of Arabic gum; 1.42% of white part of chicken egg and 21.90% of water. This composition had 16,620.105 NM-2 of shear strength; 23.14% of volatility and 90.9583 pa.det or 909.5830 poise viscosity as optimal result at eleven days of curing time. In environment resistant test, shear strength decreased about 64.33% in acid; 17.96% in water; and 1.83% in base. Storage life test of adhesive was performed in closed box at temperature 27° C and fungi grew it in fourth week.